2015
DOI: 10.1542/peds.2015-0908
|View full text |Cite
|
Sign up to set email alerts
|

Vestibular Disorders in Children With Congenital Cytomegalovirus Infection

Abstract: BACKGROUND: Congenital cytomegalovirus (CMV) infection is the leading infectious cause of neurologic disabilities and sensorineural hearing loss in children. Sensorineural hearing loss prevalence in CMV suggests a viral tropism for the inner ear. Vestibular disorders induced by CMV infection are underestimated. This is the largest and most thorough study to assess the incidence of vestibular disorders and their correlation with hearing thresholds in children with CMV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
80
2
9

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(104 citation statements)
references
References 41 publications
(39 reference statements)
13
80
2
9
Order By: Relevance
“…CMV is known to be the leading cause of nongenetic congenital HL, with 36-88% of cases in symptomatic patients and 9-12% among asymptomatic children at birth [Dollard et al, 2007]. USNHL has been described in infected children [Bernard et al, 2015]; nevertheless, the prevalence of CMVpi and its consequences on USNHL remain underevaluated. Despite strong suspicion, CMVpi could not be confirmed in some children because of the lack of PCR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CMV is known to be the leading cause of nongenetic congenital HL, with 36-88% of cases in symptomatic patients and 9-12% among asymptomatic children at birth [Dollard et al, 2007]. USNHL has been described in infected children [Bernard et al, 2015]; nevertheless, the prevalence of CMVpi and its consequences on USNHL remain underevaluated. Despite strong suspicion, CMVpi could not be confirmed in some children because of the lack of PCR.…”
Section: Discussionmentioning
confidence: 99%
“…Causality can only be assessed by PCR on urinary, blood, and salivary samples within the first weeks of life, or on DBS [Leruez-Ville et al, 2011]. However, some findings may lead one to suspect this diagnosis, such as (1) brain anomaly on imaging (white matter lesions, polymicrogyria, cortical atrophy or cerebellar hypoplasia, calcifications, and microcephaly) [Manara et al, 2011], (2) vestibular dysfunction, recognized as a marker for CMVpi [Bernard et al, 2015] (as observed in 25% of our cases), and (3) progressive HL [Royackers et al, 2013].…”
Section: Discussionmentioning
confidence: 99%
“…По современным представлениям, диагностика врожденной цитомегаловирусной инфекции у но-ворожденного ребенка основывается на обнаруже-нии ДНК цитомегаловируса методом полимеразной цепной реакции (ПЦР) в первые 3 нед жизни [1,5,8,13,15,28,29], однако ряд авторов ограничивают сроки диагностики первыми двумя неделями жизни [6,11,16,25,27,30,31]. При выделении вируса после 2-3 нед жизни уже нельзя исключить интранаталь-ное или постнатальное заражение.…”
Section: клиническая картина и диагностика врожденной цитомегаловирусunclassified
“…Последствия врожденной цитомегаловирусной инфекции Врожденная цитомегаловирусная инфекция, в от-личие от приобретенной, нередко ведет к серьезным отдаленным последствиям, таким как нейросенсорная тугоухость в сочетании с расстройствами равновесия (наиболее часто), интеллектуальная недостаточность, поведенческие расстройства, детский церебральный паралич, эпилепсия, нарушение зрения, микроцефа-лия. Риск последствий наиболее высок (до 40-65%) при симптоматической цитомегаловирусной ин-фекции [7,25,30,44]. При бессимптомном вариан-те основным неблагоприятным исходом является тугоухость -в 7-15% случаев [1,7,11,15,29,40].…”
Section: таблица клиническая характеристика врожденной цитомегаловирunclassified
“…CMV-related hearing loss is often delayed in onset, presenting after the newborn period, and can produce a progressive or fluctuating course. In addition to SNHL, vestibular disorders have also been found to occur frequently in children with congenital CMV infection [14]. …”
Section: Clinical Significance Of Congenital CMV Infectionmentioning
confidence: 99%